Dynamics associated with the state of cohabitation with examples from a few countries of the developing world: a literature review - Kang’ethe, S.M.; Mafa, Itai (MCSER Publishing, 2020)
The pace at which cohabitation is increasingly becoming a norm in many African countries presents a challenge that African countries need to address. These countries need to stop blaming globalization, modernization, eurocentrism and western centric lifestyles as reasons wreaking havoc to their institutions of marriage and cultures. The aim of article is to explore, debate and form discourses on the factors underpinning the phenomenon of cohabitation with examples from developing countries. The article has used a review of literature methodology. The following factors underpin the phenomenon of cohabitation: weakening of moral and religious fibres; individuals need for financial security and desire for social affiliation and affection; and pressure from friends and relatives to get into a relation and sire children. The following present perfidious effects of cohabitation: susceptibility to conflict and violence, poverty and HIV/AIDS; and social stigma and societal condemnation. The article urges governments, faith based education and any marriage friendly bodies to intensify education on the perfidious effects of cohabitation. These bodies need to address all the underpinning factors such as poverty that forms a palatable environment to cohabitation.